Quasi-Randomized Trial of Contact With Nature and Effects on Attention in Children - Johnson, Shannon A.; Snow, Stephanie; Lawrence, Michael A.; Rainham, Daniel G. C. (Frontiers in Psychology, 2019)
Children today spend less time in nature than previous generations and there is concern that this shift negatively impacts children’s cognitive abilities, particularly their ability to direct their attention. Theories, such as the Attention Restoration Theory (ART), suggest that contact with nature may replenish endogenous attention (e.g., directed, voluntary attention). There is a lack of rigorous research on how contact with nature is associated with attentional performance in children. This study employed a quasi-experimental design and included a sample of typically developing children to investigate performance on computerized endogenous and exogenous attention tasks before and after exposure to one of two interventions – a 30-min walk in either an urban (n = 30) or natural (forested, n = 30) environment. The two experimental groups were equivalent with regard to sex ratio, age, IQ, and connectedness to nature. Attention was assessed using the Combined Attention Systems Test (CAST), a state-of-the-art assessment tool designed to evaluate exogenous and endogenous attention characteristics. Bayesian hierarchical modeling of both response time (RT) and error rate (ER) was employed to evaluate the fixed effect of attentional measures and interactions with session and group. Consistent with predictions of ART, results support credible effects of the nature intervention on two measures of endogenous attention: Alerting RT: d = 0.85 (95% CI: 0.21–1.8), Orienting ER: d = 1.45 (95% CI: 0.17–7.18), but not on any of the measures of exogenous attention. Clinical Trial Registration:https://www.isrctn.com/, identifier ISRCTN17762011.